Wallace Stevens and the apocalyptic mode - Woodland, Malcolm, 1958- (Book collections on Project MUSE., 2005)
Wallace Stevens and the Apocalyptic Mode focuses on Stevens's doubled stance toward the apocalyptic past: his simultaneous use of and resistance to apocalyptic language, two contradictory forces that have generated two dominant and incompatible interpretations of his work. The book explores the often paradoxical roles of apocalyptic and antiapocalyptic rhetoric in modernist and postmodernist poetry and theory, particularly as these emerge in the poetry of Stevens and Jorie Graham. This study begins with an examination of the textual and generic issues surrounding apocalypse, culminating in the.